Design of vancomycin RS-100 nanoparticles in order to increase the intestinal permeability - Hadi Valizadeh; Parvin Zakeri-Milani; Mitra Jelvehgari; Badir Delf Loveymi (Tabriz University of Medical Sciences, 2012)
Purpose: The purpose of this work was to preparation of vancomycin (VCM) biodegradable nanoparticles to improve the intestinal permeability, using water-in-oil-in-water (W/O/W) multiple emulsion method. Methods: The vancomycin-loaded nanoparticles were created using double-emulsion solvent evaporation method. Using Eudragit RS100 as a coating material. The prepared nanoparticles were identifyed for their micromeritic and crystallographic properties, drug loading, particle size, drug release, Zeta potential, effective permeability (Peff) and oral fractional absorption. Intestinal permeability of VCM nanoparticles was figured out, in different concentrations using SPIP technique in rats. Results: Particle sizes were between 362 and 499 nm for different compositions of VCM-RS-100 nanoparticles. Entrapment efficiency expansed between 63%-94.76%. The highest entrapment efficiency 94.76% was obtained when the ratio of drug to polymer was 1:3. The in vitro release studies were accomplished in pH 7.4. The results showed that physicochemical properties were impressed by drug to polymer ratio. The FT-IR, XRPD and DSC results ruled out any chemical interaction betweenthe drug and RS-100. Effective intestinal permeability values of VCM nanoparticles in concentrations of 200, 300 and 400 µg/ml were higher than that of solutions at the same concentrations. Oral fractional absorption was achieved between 0.419-0.767. Conclusion: Our findings suggest that RS-100 nanoparticles could provide a delivery system for VCM, with enhanced intestinal permeability.